Anatomic Relationship of the Sural Nerve when Performing Achilles Tendon Repair using the Percutaneous Achilles Repair System, a Cadaveric Study. Issue 4 (22nd October 2020) - McGee, Roddy; Watson, Troy S.; Eudy, Adam; Brady, Candice L.; Vanier, Cheryl; LeCavalier, Daniel; Hoang, Victor C.
Category: Sports; Trauma Introduction/Purpose: Minimally-invasive techniques for Achilles tendon repair are gaining popularity by orthopedic surgeons due to the reports of similar re-rupture rates with open versus percutaneous techniques with less wound complications and quicker recovery with percutaneous methods. The goal of the study was to quantify the relationship of the sural nerve to the Percutaneous Achilles Repair System (PARS) during Achilles tendon repair and identify sural nerve violations utilizing this system. Methods: The PARS was placed into ten lower extremity cadaveric specimens after simulation of an Achilles tendon rupture. After placement of the PARS jig and passage of the needles, careful dissection was performed in order to identify whether the sural nerve was violated and the distance of the sural nerve in relation to the passed needles was recorded. Results: Of the 10 cadaveric specimens, none had violation of the sural nerve during percutaneous needle passage. Zero of the 50 (0%) needles directly punctured the substance of the sural nerve, however, one needle was found to have come into close proximity separating the sural nerve and small saphenous vein but when the suture was passed and the PARS jig removed, the nerve was found remain intact with no evidence of entrapment. Conclusion: This study demonstrated the potential risk for sural nerve injury when using the PARS for Achilles tendon repair.